De-intensification of therapy in human papillomavirus associated oropharyngeal cancer: A systematic review of prospective trials. (April 2020) - Patel, Roshal R.; Ludmir, Ethan B.; Augustyn, Alexander; Zaorsky, Nicholas G.; Lehrer, Eric J.; Ryali, Rohith; Trifiletti, Daniel M.; Adeberg, Sebastian; Amini, Arya; Verma, Vivek
Highlights: PRISMA systematic review including 10 HPV-associated de-intensification trials. Chemoradiotherapy de-escalation strategies show promising outcomes, few toxicities. Two trials showed superior outcomes with cisplatin versus cetuximab. Although de-escalations strategies differ, many feasible options exist. Long-term follow-up is required for firm treatment recommendations. Abstract: Numerous trials have been launched over the prior decade examining the safety and efficacy of therapy de-escalation in human papillomavirus (HPV)-associated oropharyngeal cancer (OPC). Because no summative assessment of these prospective trials exists to date, we systematically reviewed the outcomes and toxicities associated with therapy de-intensification for this population. PRISMA-guided systematic PubMed searches (along with articles known to the authors and references thereof) were performed for prospective studies reporting clinical outcomes and/or toxicities of de-intensified RT and/or systemic therapy (with or without surgery), exclusively for HPV-associated OPC. Ten prospective studies were analyzed. Performing a meta-analysis was not entirely possible owing to the heterogeneity of treatment paradigms and the lack of >2 studies for most paradigms; however, because just one paradigm (induction chemotherapy followed by reduced-dose RT and/or systemic therapy) had 4 associated articles, an exploratory meta-analysis was conducted for that subset. Two trials of dose-reduced concurrent chemoradiotherapy (60 Gy/weekly cisplatin) demonstrated 3-year distant metastasis-free survival and overall survival (OS) ranging from 91 to 100% and 95%, respectively; acute grade 3+ mucositis and dysphagia occurred in 33–35% and 21–39%, respectively. In the four trials of induction chemotherapy (platinum/taxane-based) followed by dose-reduced RT, 2-year progression-free and OS ranged from 80 to 95% and 83 to 98%, respectively; acute grade 3+ dysphagia, dermatitis, and mucositis ranged from 9 to 15%, 7 to 20%, and 9 to 30% (excluding one outlier), respectively. For these four trials, the exploratory meta-analysis showed a pooled 2-year PFS and OS of 89% (95% confidence interval, 80–96%) and 96% (92–99%). The pooled rates of grade ≥3 dysphagia, dermatitis, and mucositis were 13% (7–19%), 9% (5–14%), and 28% (9–53%). However, there was significant heterogeneity in the 2-year PFS (I 2 = 57%, p = 0.07) and grade ≥3 mucositis (I 2 90%, p < 0.01). Next, both randomized trials which replaced concurrent tri-weekly cisplatin with weekly cetuximab illustrated superior outcomes with the former. Lastly, two remaining trials (one using functional imaging to guide reduced-dose RT, and another examining reduced-dose postoperative RT) also showed satisfactory outcomes and toxicities. Taken together, dose-reduced chemoradiotherapy (with or without induction chemotherapy for patient/biology selection purposes) seems to be a promising de-escalation strategy for HPV-associated OPC, although replacement of concurrent cisplatin by cetuximab is not recommended. Long-term follow-up is required for firmer conclusions.